Rekayasa Simulasi CFD ANSYS Pengaruh Tinggi Siphon Terhadap Distribusi Tekanan dan Debit Air di Sepanjang Aliran Pipa pada Industri Kecil Penyedia Air Bersih - Nashrullah, Iqbal; Nugroho , Setyo ; Ulum , Achmad Bahrul (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
In the implementation of the siphon system it is used to prevent failure of rising groundwater levels that flow in the highlands including mountain slopes. The siphon system experiences greater drop pressure along with the increase in the height of the siphon, which should have higher pressure with a constant flow and an increase in the height of the siphon to achieve greater siphon system efficiency. To find out the value of pressure drop and the cause of the pressure drop on the siphon system, three methods are used, namely theoretical calculation, simulation of CFD ANSYS and actual measurements using pressure gauge water of bordoun type analogous with variations of valve opening 100% full opened, 66,67% opened, and 33,33% opened and the heights of the siphon are 1 meter, 1,5 meters and 2 meters. From the results of the three methods, the average water flow rate varies based on the height of siphon 1 meter, 1,5 meters and 2 meters is 0,0000854 m3/s to 0,0002716 m3/s and the average pressure of 111.736,7 N/m2 to 88.899,57 N/m2. While the average value of siphon based on variations in valve openings with the same height of siphon is obtained 83.939,634 N/m2 to 130.400,615 N/m2. In addition, an error value between theoretical calculation and CFD simulation of 0,03% to 1,18% and error of the between theoretical calculations and actual measurements is 0,08% to 1,10%.